INDEKS KEPUASAN MASYARAKAT TERHADAP PROGRAM CSR BUJUR BERSTAMINA: BUDIDAYA JAHE MERAH - Rahma Yuliani; Zaki Mubarak; Arifah Arifah; Norlena Norlena (Universitas Lambung Mangkurat, 2023)
Corporate social responsibility (CSR) as a community empowerment program that can improve the community's economic level. PT. DPPU Pertamina Syamsudin Noor is implementing a CSR program that focuses on red ginger nuns. This study aims to measure the community satisfaction index (IKM) for the CSR programs that have been implemented. This research is a quantitative research using 10 elements of question indicators. The research population is all the people in Sidomulyo Village 1 RT. 02 and RT. 03, Guntung Payung Village, Banjarbaru City. The sample in this study was taken using a simple random sampling technique. The results showed that the IKM score was 3.39, with a conversion value of 84.75. Based on this value, it was concluded that the IKM from the implemented CSR program was in the very good category.